Earliest Oligocene hystricognathous rodents from the Atlantic margin of northwestern Saharan Africa (Dakhla, Morocco): systematic, paleobiogeographical, and paleoenvironmental implications. Issue 5 (3rd September 2017) - Marivaux, Laurent; Adnet, Sylvain; Benammi, Mohamed; Tabuce, Rodolphe; Yans, Johan; Benammi, Mouloud
ABSTRACT: Hystricognathous rodents are among the most common members of African mammal faunas of the mid-Paleogene, but their record has so far remained limited to North and northeast Africa. Here we report the first Paleogene record of hystricognaths from the Atlantic margin of North Africa. The fossils come from the westernmost part of the Sahara, east of the Dakhla peninsula, Morocco, from estuarine deposits dating to the earliest Oligocene (Dakhla level C2 [DAK C2 ]). Several tens of isolated teeth plus three jaw fragments document seven species of hystricognaths ( Gaudeamus cf. aslius, G. cf. hylaeus, Phenacophiomys occidentalis, gen. et sp. nov., Birkamys aff. korai, Mubhammys atlanticus, sp. nov., Neophiomys minutus, sp. nov., and ? Phiocricetomys sp.). Despite the extensive east-west geographic distance, the majority of hystricognath taxa recorded in DAK C2 document primarily close relatives of taxa that are known from a latest Eocene Egyptian locality (L-41) and from early Oligocene localities of both Egypt and Libya. This highlights the widespread east-west distribution of hystricognaths across North Africa, a distribution that reflects the existence of roughly similar tropical environmental conditions in northern latitudes of Africa at that time. The presence of seven hystricognath species plus five anomaluroid species in sympatry during the earliest Oligocene demonstrates that rodents were particularly diverse near the global cooling recorded at the Eocene-Oligocene transition. We describe and compare the species and new species of hystricognaths with their sub-coeval counterparts from northern and northeastern Africa and then discuss the paleobiogeographic and paleoenvironmental implications of that discovery. http://zoobank.org/urn:lsid:zoobank.org:pub:4041680F-65A0-41D5-AF97-D6115A656F15 Citation for this article: Marivaux, L., S. Adnet, M. Benammi, R. Tabuce, J. Yans, and M. Benammi. 2017. Earliest Oligocene hystricognathous rodents from the Atlantic margin of northwestern Saharan Africa (Dakhla, Morocco): systematic, paleobiogeographical, and paleoenvironmental implications. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1357567.